Treatment of medication-related osteonecrosis of the jaw with cell therapy - Bouland, Cyril Lucien; Javadian, Rokneddine; Gilis, Sarah; Yanni, Antoine; Le Clercq, Maxime; Mestrallet, Pierre; Kampouridis, Stelianos; Bron, Dominique; Lalmand, Martin; Vanden Eynden, Xavier; Boutremans, Edward; Dequanter, Didier; et al. (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Medication-related osteonecrosis of the jaw (MRONJ) poses a significant challenge considering the absence of a “gold standard” treatment. Cell-based therapy and tissue engineering offer promising therapeutic alternatives. This study aimed to harness the regenerative properties of adipose-tissue stromal vascular fraction (AT-SVF) and leukocyte-platelet-rich fibrin (L-PRF) for MRONJ treatment. AT-SVF contains mesenchymal stromal cells (MSC) and endothelial progenitor cells (EPC), which promote bone formation, while the L-PRF scaffold can serve as a three-dimensional scaffold for the AT-SVF and support tissue healing through growth factor release. Materials and Methods: The protocol involved applying autologous AT-SVF within an L-PRF matrix following surgical debridement. Age, gender, body mass index, comorbidities, underlying oncological condition, prescribed antiresorptive treatment: BP or DMB, antiresorptive treatment duration, antiresorptive treatment potential discontinuation, number of MRONJ lesion, MRONJ location, MRONJ stage, MRONJ trigger factor were assessed for each patient. Patients underwent the procedure and were monitored for a minimum of six months based on clinical, biological and medical imaging criteria. Results: Nine patients, with a total of ten MRONJ lesions, participated in the study. Six patients were female, and three were male, with a mean age of 68±8 years. Four patients had multiple myeloma (MM), three had metastatic breast cancer, and two had metastatic prostate cancer. Seven MRONJ cases were classified as stage II, and three were classified as stage III. Soft tissue completely healed within a month after treatment in nine cases, with no clinical improvement observed in the remaining case. During follow-up, no sign of MRONJ recurrence was observed. Tridimensional medical imaging revealed bone healing six months after the surgical procedure. Immunophenotyping confirmed the presence of MSC and EPC in the AT-SVF: 12,6±4,5% CD31+, 20.5±7,8% CD34+, 34,4±7,3% CD146+ and 54,6±7,4% CD45+. Conclusion: This prospective study introduces a potential new treatment approach for MRONJ using autologous AT-SVF within an L-PRF scaffold. Our results are encouraging and suggest the need for further investigation with a larger patient cohort to better understand the underlying mechanisms.